CCAAT/enhancer binding protein α (C/EBPα)+ M2 macrophages contribute to fibrosis in IgG4-related disease?. Issue 3 (May 2015) - Yamamoto, Motohisa; Shimizu, Yui; Takahashi, Hiroki; Yajima, Hidetaka; Yokoyama, Yoshihiro; Ishigami, Keisuke; Tabeya, Tetsuya; Suzuki, Chisako; Matsui, Mikiko; Naishiro, Yasuyoshi; Imai, Kohzon; Shinomura, Yasuhisa
Abstract IgG4-related disease (IgG4-RD) is a new disease entity characterized by type 2 helper T (Th2)-dominant inflammation and progressive fibrosis. We found the infiltration of strange cell populations in the fibrotic lesions of submandibular gland specimens obtained from 15 patients with IgG4-RD. These cells expressed CCAAT/enhancer binding protein a (C/EBPα). Many of the cell populations were identified with M2 macrophages. The degrees of infiltration of C/EBPα+M2 macrophages and the ratio of fibrotic lesions in the specimens were correlated (r2 = 0.83, p < 0.01). We also analyzed the expression of C/EBPα in other chronic inflammatory disorders: synovium in rheumatoid arthritis (RA), liver tissue in chronic viral hepatitis, and mucosa in ulcerative colitis. The specimens from RA and chronic viral hepatitis showed infiltration of C/EBPα+ cells, but there were few C/EBPα-positive cells in ulcerative colitis. Fibrosis is not a major issue in ulcerative colitis. In conclusion, we found the remarkable infiltration of C/EBPα+M2 macrophages in cases of chronic inflammation with fibrosis, including IgG4-RD. This primitive study also disclosed that most of C/EBPα+M2 macrophages localized in fibrotic lesions, and the degree of the infiltration and the ratio of fibrotic area were correlated.